1995
DOI: 10.1111/j.1365-2125.1995.tb05777.x
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular and subjective effects of thyrotropin releasing hormone (TRH) and a stable analogue, dimethyl proline‐TRH, in healthy volunteers.

Abstract: Heart rate was more transiently elevated (peak Aheart rate: 9.0 beats min-) during the first 6 min post infusion. 5 Mild apprehension was reported for the first 6 min after RX77368 1 mg, whereas paraesthesiae were noted after TRH. Otherwise both drugs were similar in the type (flushing, nausea, acid taste, urethral sensations) and duration of subjective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The mechanisms responsible for these adverse effects have not been fully elucidated; however, in humans, TRH transiently increases sympathetic tone and may induce release of serotonin in the gastrointestinal tract. 8 During experiment 1, in which the 2 TRH stimulation tests were performed within 24 hours, the median delta ACTH response for the second test was significantly lower than that for the first test. This suggested that stored ACTH is released when TRH receptors are stimulated, and those stores cannot be replenished within 24 hours.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The mechanisms responsible for these adverse effects have not been fully elucidated; however, in humans, TRH transiently increases sympathetic tone and may induce release of serotonin in the gastrointestinal tract. 8 During experiment 1, in which the 2 TRH stimulation tests were performed within 24 hours, the median delta ACTH response for the second test was significantly lower than that for the first test. This suggested that stored ACTH is released when TRH receptors are stimulated, and those stores cannot be replenished within 24 hours.…”
Section: Discussionmentioning
confidence: 87%
“…Human patients also report adverse effects associated with TRH administration, such as flushing of the skin, nausea, urethral sensations, acidic taste, apprehension, and paresthesia. 8 Transient coughing, vomiting, excessive salivation, and defecation have been observed in dogs 9 and cats 10 after TRH (0.9 to 1.1 mg, IV) administration. The mechanisms responsible for these adverse effects have not been fully elucidated; however, in humans, TRH transiently increases sympathetic tone and may induce release of serotonin in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…TRH is a tripeptide neurotransmitter found in multiple brain regions and in some peripheral organs [Merchenthaler et al, 1985;Morley, 1979]. In studies of its cardiovascular and subjective effects, healthy subjects report nausea, apprehension, palpitations, paraesthesia, and hot and cold flushes, which are symptoms that occur during panic attacks [Coupland et al, 1995]. However, TRH administered to PD patients did not provoke panic attacks [Tancer et al, 1990;Uhde, 1990, 1991].…”
Section: Introductionmentioning
confidence: 99%